(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the results of using audio texts while teaching the Russian language to students of universities of Kazakh departments as a non-native language. There are recommendations on the use of such listening mechanisms as speech hearing, memory, probabilistic prediction and articulation. Particular attention is paid to various ways of using audio texts in the educational process, aimed at developing skills of listening and speaking. The article presents a complex of exercises using audio texts that form skills and experience of oral speech based on listening.